Analisis Komparatif dalam Memprediksi Kebangkrutan pada Perusahaan Telekomunikasi yang Listing di Bursa Efek Indonesia Tahun 2008-2017 - Maylani Wulandari; Abel Tasman (Jurnal Kajian Manajemen dan Wirausaha, 2019)
The purpose of this research is to explain the different score from some prediction of bankruptcymodel, that are Altman Modification, Springate, and Zmijewski. The object of this research istelecomunication companies that listed in Indonesian Stock Exchange (IDX) from 2008-2017. Toanalyze the data, this research used Wilcoxon Match Pair T-test to answer hypothesys 1, 2, and 3and hypothesys 4 used Accuration Test. The result is Wilcoxon Match Pair T-test are thatAltman, Springate, and Zmijewsk’s was not have different score to predict bankruptcy oftelecomunication companies. Meanwhile the result of accuration test showed the highest modelto predict of bankruptcy in telecomunication companies is Zmijewski’s model with 89%, then64% for Altman, and the lower is 62% to Springate’s model.Keywords: Brand Personality, Service Quality, Store Atmosphere, Repurchase Intention